EFL Lectures’ Grading Practices in Islamic and General Higher Education Institutions - Sri Mulyani; Ahmad Ardillah Rahman; Fatmawati Akhmad; Hardiani Ardin (Indonesian TESOL Journal, 2023)
This study investigates EFL lecturers’ grading practices, focusing on the beliefs underlying these practices, the types of assessment they implement to determine students’ final grades, and multiple factors influencing them in deciding students’ final grades. Applying interpretative phenomenological analysis (IPA), two EFL lecturers, one from an Islamic higher education institution and the other from a general higher education institution, were interviewed to reveal their grading practices. The findings of the research reveal that both lecturers believe that grades should reflect students’ learning outcomes. They serve as an instrument to measure the achievement of learning objectives and to identify which items from the course need to be improved. Both lecturers also believe that assigning final grades should involve multiple aspects related to moral character development. Furthermore, they apply various types of assessment. They employ formal and informal assessment types to obtain students’ scores before deciding their final grades. In addition, they consider academic factors, such as scores derived from formal and informal assessments, and non-academic factors, such as students’ efforts, attitude, and attendance, should be employed in their grading practices.     Keywords: Grading practices; Assessment; Academic Factors; Non-academic Factors